The Effect Of Implementation Of DMO And DPO On Indonesian Palm Oil Exports - Djamarel HERMANTO; Lisnatiawati SARAGIH (Journal of Tourism Economics and Policy, 2023)
This study aims to determine and analyze (1) the effect of Domestic Market Obligation, DMO, implementation and partial, Domestic Price Obligation, DPO, implementation on Indonesian palm oil exports and (2) the effect of simultaneous DMO implementation and DPO implementation on Indonesian palm oil exports. The results of the Pearson correlation test on the variables of DMO implementation and DPO implementation had a powerful/close relationship with palm oil exports. The regression test results, simultaneously with the F test and partially with the t-test, show that the implementation of DMO and the implementation of DPO have a significant effect on Palm Oil Exports.